Comparative study of different storage bed designs of a solid-state hydrogen tank. (December 2019) - Manai, Mohamed Sakreddine; Leturia, Mikel; Pohlmann, Carsten; Oubraham, Jorn; Mottelet, Stéphane; Levy, Michael; Saleh, Khashayar
Highlights: Numerical simulation of hydrogenation in different metal hydride bed configurations. Analysis of the effect of heat transfer management on system dynamics. Predictive simulation to optimize heat transfer and hydrogenation rates. Abstract: This work discusses the influence of different metal hydride storage bed configurations. The objective was to design and optimize a solid-state hydrogen storage for a nonpolluting mobility. A study of the absorption and desorption dynamics of a loose powder bed was performed first, followed by three different storage bed configurations: compacted Ti-Mn alloy powder, alternated Ti-Mn alloy compacts with stainless steel fins and compacted [Ti-Mn alloy/Stainless steel] powder mixture. A numerical model was developed to simulate the heat transfer and the hydrogen absorption and desorption rates. The alternation and compact mixture configurations gave better heat transfer efficiencies, absorption and desorption rates and increased hydrogen storage densities. Indeed, an efficient heat transfer (between the tank and its surrounding fluid), a tailored porosity of the metal hydride storage bed and the addition of high thermal conductivity materials allowed the overall storage performance to be improved. Thus, the required time for loading/unloading hydrogen was reduced drastically. The alternation configuration would offer the additional advantage of a simple, inexpensive and efficient recycling procedure.